The Impact of E-wallet Online Payments on Increasing MSME Sales in Mojosari Village - Mufidatunnisa; Lucky Al-Hafzy (Al Urwah : Sharia Economics Journal, 2025)
This study analyzes the influence of e-wallet adoption on the sales performance of food and beverage MSMEs in Mojosari Village amidst digital payment trends and infrastructure challenges. The study aimed to analyze the driving factors, customer perceptions, and barriers to e-wallet implementation such as DANA, GoPay, and ShopeePay. This quantitative descriptive study used purposive sampling of 100 productive-age respondents (17-30 years old) who actively use digital wallets, using nominal and ordinal scale questionnaires plus semi-structured interviews. Data analysis applied descriptive statistics including frequency distribution, percentages, and tables using SPSS. The results showed a 98.7% adoption rate dominated by DANA (71.61%), driven by ease of use, security features, and cashback promotions, but hampered by unstable internet connections, transaction costs, and digital trust. E-wallets improve transaction efficiency and customer appeal. The conclusion emphasizes multi-stakeholder collaboration for the sustainable digital transformation of rural MSMEs